2000
DOI: 10.1093/jexbot/51.351.1687
|View full text |Cite
|
Sign up to set email alerts
|

Rubisco activation state decreases with increasing nitrogen content in apple leaves

Abstract: Based on the curvilinear relationship between leaf nitrogen content and the initial slope of the response of CO(2) assimilation (A:) to intercellular CO(2) concentrations (C:(i)) in apple, it is hypothesized that Rubisco activation state decreases with increasing leaf N content and this decreased activation state accounts for the curvilinear relationship between leaf N and CO(2) assimilation. A range of leaf N content (1.0-5.0 g m(-2)) was achieved by fertilizing bench-grafted Fuji/M.26 apple (Malus domestica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
88
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 172 publications
(107 citation statements)
references
References 41 publications
16
88
0
3
Order By: Relevance
“…Total Rubisco activity was measured after incubating the peel extract in the assay solution for 15 min at room temperature as described previously (Cheng and Fuchigami 2000).…”
Section: Analysis Of Leaf Pigments and Proteinsmentioning
confidence: 99%
“…Total Rubisco activity was measured after incubating the peel extract in the assay solution for 15 min at room temperature as described previously (Cheng and Fuchigami 2000).…”
Section: Analysis Of Leaf Pigments and Proteinsmentioning
confidence: 99%
“…Total Rubisco activity was measured after incubating the leaf extract in the assay solution for 15 min at room temperature as described previously (Cheng and Fuchigami 2000).…”
Section: Assay Of Photosynthetic Enzymesmentioning
confidence: 99%
“…The other hypothesis is related to the fraction of inactive Rubisco. Previous studies have shown that the activation state of Rubisco declines as leaf N (Cheng and Fuchigami 2000) or Rubisco (Eichelmann and Laisk 1999) contents increase. Furthermore, in this study, the fraction of N allocated to Rubisco appeared to be higher than those previously reported values for tree species (Fig.…”
Section: Discussionmentioning
confidence: 97%